Karakteristik Penderita Kanker Ovarium di RS Ibnu Sina Makassar - Muthmainnah, Putri Rahayu; Syahril, Erlin; Rahmawati; Mona Nulanda; Anna Sari Dewi (Universitas Muslim Indonesia, 2023)
Ovarian cancer is condition caused by abnormal tissue that growth in ovary . Ovary is female reproductive organs where eggs are produced. There is three Ovarian cancer is classified as an epithelial tumor that develops on the surface of the ovary, originating germ cell tumors from in producing cells egg can found in women young, and tumors of stromal origin from cells that have hormone womanhood namely estrogen and progesterone. Objective to find out the characteristics of ovarian cancer sufferers at Ibnu Sina Makassar Hospital. Method this research is a descriptive research with design studies cross sectional , the researcher will collect secondary data through record medical patient ovarian cancer at Ibnu Sina Makassar Hospital. The results shows that from 90 samples, characteristics patients based on age the most is 46-55 years totaling 29 people (32.2%), marital status is already married totaling 76 people (84.4%), symptoms clinical is stomach grow totaling 55 people (61.1%), stage of cancer is stage IIIC totaling 32 people (35.6%), type histopathology is an epithelial tumor surface totaling 73 people (81.1%), and most abdominal ultrasound images on smooth tumor walls totaling 48 people (53.3%), no septate totaling 37 people (41.1%), echogenicity mixed echoic totaling 38 people (42.2%). Can concluded that characteristics the most found at the age of 46-55 years, marital status is already married, symptom clinical is stomach enlarged, cancerous stage is stage IIIC, type histopathology is an epithelial tumor surface, and abdominal ultrasound image of the smooth tumor wall, no septate, echogenicity mixed echoic.